2017
DOI: 10.1111/jgs.15151
|View full text |Cite
|
Sign up to set email alerts
|

Medications That Cause Dry Mouth As an Adverse Effect in Older People: A Systematic Review and Metaanalysis

Abstract: OBJECTIVES:To assess and quantify the risk of druginduced dry mouth as a side effect in older people. DESIGN: Systematic review and metaanalysis. SETTING: A search of the literature was undertaken using Medline, Embase, Cochrane, Web of Science, and PubMed from 1990 to 2016. PARTICIPANTS: Older people (aged ≥60) who participated in intervention or observational studies investigating drug use as an exposure and xerostomia or salivary gland hypofunction as adverse drug outcomes. MEASUREMENTS: Two pairs of author… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
90
0
14

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(105 citation statements)
references
References 60 publications
1
90
0
14
Order By: Relevance
“…mouth dryness both in 2007 and in 2012) and incident mouth dryness in both cohorts, most strongly so with xerostomia reported during daytime (Table ). Previous studies have confirmed associations between intake of various medicines and xerostomia . However, few have adjusted for confounding factors reflecting the underlying health conditions for which medication was prescribed .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…mouth dryness both in 2007 and in 2012) and incident mouth dryness in both cohorts, most strongly so with xerostomia reported during daytime (Table ). Previous studies have confirmed associations between intake of various medicines and xerostomia . However, few have adjusted for confounding factors reflecting the underlying health conditions for which medication was prescribed .…”
Section: Discussionmentioning
confidence: 99%
“…Whereas a number of studies have examined cases of serious mouth dryness caused by immune‐system conditions, such as Sjøgren's syndrome, many older adults demonstrate dry mouth as a consequence of other systemic diseases and medications . Epidemiological studies have shown an increase in the prevalence of dry mouth with increasing age, although ageing per se is not a major risk factor for xerostomia .…”
mentioning
confidence: 99%
“…Hence, drug-induced dry mouth is one of the most common oral problems in elderly individuals. 34 Our data showed a significantly higher mean number of administered medicines among the subjects presenting oral dryness symptoms compared to these with no symptoms. Similar observations were made by Bogucki et al, who identified a correlation between xerostomia, medication taken by patients, age, gender and past diseases.…”
Section: Discussionmentioning
confidence: 44%
“…Idosos com baixos níveis de secreção salivar podem apresentar prejuízos funcionais: paladar, fala e dificuldades para mastigar e deglutir os alimentos 20 . O uso de medicamentos está associado tanto à sensação de boca seca quanto à hipofunção da glândula salivar 21 .…”
Section: Discussionunclassified